Zero deforestation agreement in Colombia - CGIAR Research Program on Water, Land and Ecosystems (2020)
Lead of the technical Secretariat of the multi-stakholder platform as part of Colombian Ministry of Environment and Sustainable Development’s Sustainable Land Use Systems (SLUS)